2020
DOI: 10.1038/s41598-020-71012-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring C4–CAM plasticity within the Portulaca oleracea complex

Abstract: Portulaca oleracea is a c 4 herb capable of performing cAM under drought stress. it is distributed worldwide and is either considered a polymorphic species or a complex of subspecies, due to its numerous morphological variations. We evaluated cAM plasticity within P. oleracea genotypes since the complexity surrounding this species may be reflected in intraspecific variations in photosynthetic behavior. eleven subspecies of P. oleracea from distant geographical locations and one cultivar were morphologically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 76 publications
0
26
0
1
Order By: Relevance
“…tend to inhabit environments with high light intensities, weak CAM acidity of purslane plants under high salinity in this study could be due to the low level of light used to cultivate this plant species. Furthermore, there are different CAM expression levels within the P. oleracea complex ( Ferrari et al, 2020 ). Under drought stress, when CAM was induced in purslane, lower qP, and higher NPQ were observed ( D’Andrea et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…tend to inhabit environments with high light intensities, weak CAM acidity of purslane plants under high salinity in this study could be due to the low level of light used to cultivate this plant species. Furthermore, there are different CAM expression levels within the P. oleracea complex ( Ferrari et al, 2020 ). Under drought stress, when CAM was induced in purslane, lower qP, and higher NPQ were observed ( D’Andrea et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the CO 2 fluxes increased during the light and the dark, reverting to a non-CAM pattern within 24 h after re-watering. Ferrari et al (2020) evaluated CAM plasticity of 11 subspecies of P. oleracea from distant geographical locations, and they concluded that all subspecies expressed CAM in a fully-reversible manner. However, there are different combinations of CAM expression level within the P. oleracea complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, molecular docking simulation was conducted on polysaccharides derived from the extract of Portulaca oleracea to assess their ability to inhibit the SARS-CoV-2 protease. Portulaca oleracea (duckweed) is an annual succulent in the Portulacaceae family with slight hogweed or parsley which may reach 16 inches in height [36]. Molecular docking permits rapid screening of the sequences of amino acid through many coronaviruses' species such as SARS-CoV-2 [23,37].…”
Section: Research Articlementioning
confidence: 99%
“…A detailed survey of photosynthetic gene activity has only been completed in one Portulaca species, P. oleracea (Ferrari et al 2020b(Ferrari et al , 2020c, which focused on CCM gene identification in an NADtype C4 species. Similar experiments on other Portulaca species are needed to answer fundamental questions about the function and evolution of C4+CAM, and the integration of new metabolic modules more generally.…”
mentioning
confidence: 99%